Early Childhood Development of Integrative Holistic Design in Non-Formal Early Childhood - Sagala, Anita Chandra Dewi; Khasanah, Ismatul (Indonesian Journal of Early Childhood Education Studies, 2015)
The aim of this study is to: (1) making of the early childhood development design of integrative holistic in non-formal early childhood (2) provide appropriate services for integrative holistic to early childhood in the womb until six years old (3) How can early childhood development of holistic integrative design can provide services ranging from health, nutrition, parenting and education for early childhood, (4) How to integrate BKB, early childhood post, and appropriate HC thus it was born the integrative holistic assessment models. The methodology of this research was Research and Development of an option because it has a more complex process in stages to accommodate the diverse interests of this research. (Borg & Gall & 1989:784-785). The hypothesis could be given of this study were (1) an integrative holistic design applied in a non-formal early childhood in this case of integrated ECH post with BKB and HC is highly effective as compared to early childhood services are only performed by itself. (2) services that can be provided in early childhood education can be an integrative holistic health services ranging from prenatal care until after delivery, healthy children aged 0 - 6 years, knowledge of nutrition during pregnancy to nutrition for a growing child development, and education for children aged 0-6 years as the appropriate stimulation for children aged 0 - 6 years, (3) This integrative holistic early childhood education design can be integrated starting from registration, weighing, growth monitoring, nutrition services, and education and health services for early childhood, (4) The results of an increase in parental knowledge about nutrition issues, health and education can be seen from the results of pre-tests and post-tests were conducted, which shows that the score of the output means pretest = 11.63 less than the posttest means = 20.25. So the average of posttest score was better than the pretest score of 16.14%.How to citeSagala, A., & Khasanah, I. (2015). Early Childhood Development of Integrative Holistic Design in Non-Formal Early Childhood. Indonesian Journal of Early Childhood Education Studies, 4(1), 1-10. doi:10.15294/ijeces.v4i1.9456